Прогнозна оцінка повної технологічної енергоємності продукції чорної металургії України за виробничими схемами до 2040 року - Kuts G.O.; Teslenko O.I. (General Energy Institute of the National Academy of Sciences of Ukraine, 2021)
The perspective development of ferrous metallurgy of Ukraine for the period up to 2040 is considered. This development will take place due to structural changes of production schemes and technological measures with more effective characteristics of energy resources, energy carriers, and raw materials that directly influence the energy intensity of metallurgical products. The existing energy intensity calculations techniques were advanced and the total technological energy intensity of ferrous metallurgy products was calculated.Comparison of indicators of total technological energy intensity of final products of ferrous metallurgy (rolled metal) showed that rolled products produced by the latest energy-efficient technological schemes, which are projected to be implemented by 2040, will reduce total technological energy intensity up to 20% less than similar technological schemes used since 2017.For example, the total technological energy consumption of rolled billets of oxygen-converter steel will decrease by 17.2% (in terms of physical volume in the forecasted 2040 will be 862.293 kg c.e./t compared to the base 2017 – 1042.044 kg c.e./t), scrap process steel by 8.9% (respectively 923.999 kg c.e./t and 1014.120 kg c.e./t) and electric arc steel by 20% (703.292 kg c.e./t and 878.913 kg c.e./t). Regarding coke production, the total technological energy consumption of coke is projected to decrease by 24.0%: in 2040 it will be 210.040 kg c.e./t (in the base year 2017 it is equal to 244.585 kg c.e./t), and coke oven gas by 16.0%. , 4% (respectively 33.468 kg c.e./t and 38.72 kg c.e./t).The analysis of the role of components of energy intensity of products, namely for such products as iron ore, blast furnace coke, coke oven gas, and pig iron was made. The main components are energy resources, the share of which in the energy intensity of products is from 60 to 90%, and for other products, it is a raw material, the shares of which are within the same ranges. The main component in the structure of the formation of the total technological energy consumption of rolled products is the initial energy consumption of raw materials, the value of which is in the range of 90–92%.